2022
DOI: 10.3390/nu14071406
|View full text |Cite
|
Sign up to set email alerts
|

Low-Carbohydrate Diets and Mortality in Older Asian People: A 15-Year Follow-Up from a Prospective Cohort Study

Abstract: The long-term effects of a low-carbohydrate diet (LCD) on mortality, accounting for the quality and source of the carbohydrate, are unclear. Hence, we examined the associations of LCDs with all-cause and cause-specific mortality in a prospective cohort study. A total of 20,206 participants (13.8% diabetes) aged 50+ years were included. Overall, vegetable-based and meat-based LCD scores were calculated based on the percentage of energy as total and subtypes of carbohydrates, fat, and protein. Cox regression ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Finally, 17 publications were included for this meta-analysis. 8,12–15,17–21,29–33,41,42 Seven publications (13 studies) reported effect sizes for CVD, 8,12–17 3 (3 studies) for CHD, 12,13,16 2 (2 study) for stroke, 14,31 12 (16 studies) for all-cause mortality, 8,15,17–21,30,32,33,41,42 and 8 (10 studies) for cardiovascular mortality. 8,12,15,17,21,30,41,42…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 17 publications were included for this meta-analysis. 8,12–15,17–21,29–33,41,42 Seven publications (13 studies) reported effect sizes for CVD, 8,12–17 3 (3 studies) for CHD, 12,13,16 2 (2 study) for stroke, 14,31 12 (16 studies) for all-cause mortality, 8,15,17–21,30,32,33,41,42 and 8 (10 studies) for cardiovascular mortality. 8,12,15,17,21,30,41,42…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 17 publications were included for this meta-analysis. 8,[12][13][14][15][17][18][19][20][21][29][30][31][32][33]41,42 Seven publications (13 studies) reported effect sizes for CVD, 8,12-17 3 (3 studies) for CHD, 12,13,16 2 (2 study) for stroke, 14,31 12 (16 studies) for allcause mortality, 8,15,[17][18][19][20][21]30,32,33,41,42 and 8 (10 studies) for cardiovascular mortality. 8,12,15,17,21,30,41,42 Characteristics of studies Furthermore, the sample size (from 924 to 371 159) varied widely across these 17 studies.…”
Section: Reviewmentioning
confidence: 99%
“…Regarding the long-term efficacy of LCD on mortality, the quality and source of carbohydrates have been investigated in a prospective cohort study. The protocol included 20,206 cases (including 13.8% with diabetes), and vegetable-and meat-based LCD scores were calculated for hazard ratios (HRs) [15]. Concerning the data from the highest vs. lowest quartiles, vegetable-based LCD showed HRs of 1.16 and 1.30 for all-cause and CVD mortality, respectively.…”
Section: Commentarymentioning
confidence: 99%